3D Bioprinting: from Benches to Translational Applications - Heinrich, Marcel Alexander; Liu, Wanjun; Jimenez, Andrea; Yang, Jingzhou; Akpek, Ali; Liu, Xiao; Pi, Qingmeng (Wiley-V C H Verlag Gmbh, 2019)
Over the last decades, the fabrication of 3D tissues has become commonplace in tissue engineering and regenerative medicine. However, conventional 3D biofabrication techniques such as scaffolding, microengineering, and fiber and cell sheet engineering are limited in their capacity to fabricate complex tissue constructs with the required precision and controllability that is needed to replicate biologically relevant tissues. To this end, 3D bioprinting offers great versatility to fabricate biomimetic, volumetric tissues that are structurally and functionally relevant. It enables precise control of the composition, spatial distribution, and architecture of resulting constructs facilitating the recapitulation of the delicate shapes and structures of targeted organs and tissues. This Review systematically covers the history of bioprinting and the most recent advances in instrumentation and methods. It then focuses on the requirements for bioinks and cells to achieve optimal fabrication of biomimetic constructs. Next, emerging evolutions and future directions of bioprinting are discussed, such as freeform, high-resolution, multimaterial, and 4D bioprinting. Finally, the translational potential of bioprinting and bioprinted tissues of various categories are presented and the Review is concluded by exemplifying commercially available bioprinting platforms.
Keywords: 3D bioprinting; additive manufacturing; bioinks; regenerative medicine; tissue engineering